South China Sea : time to change the name - Yang Razali Kassim (2015)
The latest ASEAN summit has not thrown up any significant sign of an early resolution to the South China Sea disputes. As leaders pursue the necessary path of diplomacy, more decisive actions may be needed, including a change of name to the “Southeast Asia Sea”.